Representing Romanticism in Fadhel Chaker's Songs: A Semiotic Analysis of Roland Barthes and William Wordsworth's Concept of Romanticism - Haris Khoirurrijal; Edi Komarudin; Asep Supianudin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Arabic song lyrics serve not only as a form of entertainment but also as a medium for representing cultural values and emotional experiences. However, studies on the representation of romanticism in contemporary Arabic song lyrics, particularly through Roland Barthes' semiotic approach combined with William Wordsworth's concept of Romanticism, remain limited. Therefore, this study aims to analyze the representation of romanticism in the lyrics of Fiin Layalik, Ma'qool, and Ya Ghayyeb by Fadhel Chaker through denotative, connotative, and mythical meanings. This research employed a qualitative approach using the library research method. The data consisted of words, phrases, and clauses found in the song lyrics, collected through documentation and note-taking techniques, and analyzed interpretatively using Roland Barthes' semiotic theory and William Wordsworth's concept of Romanticism. The findings reveal that romanticism is represented through four main themes: longing and loss, loneliness and nostalgia, emotional dependence and sacrifice, and destiny and the idealization of the beloved. At the denotative level, the lyrics portray acts of longing, waiting, remembering, and questioning romantic relationships. At the connotative level, these signs represent longing, loss, loneliness, nostalgia, emotional dependence, sacrifice, and the idealization of the beloved. At the mythical level, love is constructed as a profound emotional experience associated with loyalty, sacrifice, and belief in destiny. This study contributes to the development of semiotic studies in Arabic literary and song lyric analysis by demonstrating that romanticism in song lyrics functions not only as an expression of individual emotions but also as a cultural construction that shapes how people understand love and romantic relationships.